The Political Aspect of Cartoons: Rediscovering the Power of Print Media (Scientific Researches in Academia, 2024)
Cartoons in print media portray social reality through the satire of political scenarios. The regular cartoons in Nepali newspapers quite frequently raise an evoking, critical awareness about contemporary political, social, and cultural issues. This paper will analyze one cartoon from each of four popular Nepali cartoonists. Such cartoons will be sifted for their use of Nepali colloquialisms, texture, colors, signs, symbols, roles of mythical characters, etc., to critique current issues with the sharpness they deserve. The analysis is going to be framed using the last three pillars of Marshall Fishwick's Seven Pillars of Popular Culture: Logos, Ethos, and Mythos. To elaborate further on these cartoons, perspectives of Dominic Strinati about popular culture, structuralism, and semiology will be used. The wider reach of cartoons in the dailies within Nepal enjoys a sure means of communicating an idea or message to the public. This study tries to explain how these two elements instituted potent social and political commentary and built higher levels of critical consciousness among citizens on contemporary issues. This paper will deconstruct the linguistic and visual elements that make Nepali cartoons a strong medium of social critique and reflection.